Ansiedad y su repercusión en sus relaciones interpersonales de una paciente de 44 años - Vargas Vélez, Erick Francisco (2023)
In the following case study, it was carried out with the purpose of establishing the effect of the problem of a 44-year-old patient who suffers from anxiety and affects her interpersonal relationships, as was the origin of her problem, and it is also given to know the treatment he had for his recovery. For which we worked with the application of cognitive behavioral therapy with its different types of techniques according to each affected area, each symptom was detailed for each area. A psychometric test, the Hamilton Anxiety Scale, was also applied to measure the degree of anxiety that the patient had, through which Generalized Anxiety Disorder was determined as a diagnosis, so that conditions unhealthy interpersonal relationships in addition to presenting anguish , fear and stress, taking as a guideline the criteria provided by the DSM-V Manual with the code 300.02 and in the CIE 10 Manual with the code F41.1, followed by a therapeutic intervention scheme to work on the evolution of the patient.